Contribution of high turbidity to tidal dynamics in a curved channel in Zhoushan Islands, China - Li Li; Fangzhou Shen; Zhiguo He; Gangfeng Ma; Jiachen Wang; Kailong Huangfu (Engineering Applications of Computational Fluid Mechanics)
The curved tidal channel, Luotou Deep-water Navigational Channel, is the main channel of the Ningbo Zhoushan Port, which is ranked first in the world. Tidal dynamics in the channel are spatially and temporally asymmetric. In this study, the three-dimensional tidal dynamics in the channel were analyzed using field data and simulated using FVCOM. The results show that the tides in the channel flood/ebb along the northern/southern bank near the bottom/surface layer and these asymmetries are due to the imbalanced Coriolis force, centrifugal force, sea-level gradient, and density gradient. Residual current velocity peaks (0.7 m/s) in the middle of the channel as the same distribution as sediment flux. There are two high turbidity zones (>4 kg/m3) which are northern at flood than at an ebb in the channel. The drag reduction effect of fluid mud enhances the lateral circulation, which is strong near the Chuanshan Peninsula and frictional dissipation plays an important role in it. The presence of suspended sediment changes the contribution of acceleration terms through impacting density and bottom friction, and the centrifugal force term has the largest increases. This study provides the foundation for the morphology evolution and harbor management of macro-tidal turbid coastal zones.Highlights A baroclinic model was built to study the tidal dynamics in macro-tidal turbid Zhoushan Islands.Asymmetric tides and lateral circulation occur in the Luotou Deep-water Navigational Channel (DNC).Mechanism of lateral circulation depends on tidal phases and locations in the DNC.Sediment impacts water density and drag coefficient, and then changes currents and sediment fluxes in the DNC.